"We always have a hope that one day we’ll go back”: A qualitative interview study of life and activism in exile - Ydman,Elisabet (2018)
In the aftermath of the 2011 Bahraini uprising, many activists were forced into exile. This thesis is based on Skype interviews with exiled activists from Bahrain, who continue to engage with activism in exile. By discussing the research question of how political voice changes when an activist is forced into exile, the aim of the study is to better understand the dynamics of activism in the context of forced exile. Both the personal and the political life in exile is studied. The theoretical framework that is employed is based on the concepts of exit and voice, as originally coined by Albert Hirschman and developed by Guillermo O’Donnell. The qualitative interview is followed by grounded theory analysis, which is used to categorize the interview material. In short, the analysis addresses the themes of responsibility, reach in exile, credibility of voice, ethics of engaging with activism in exile and safety. Additionally, feelings of distance and guilt, time, and thoughts on exile and return are themes that address the more personal aspects of exile. The analysis shows advantages and disadvantages of using political voice in exile, as well as the difficulties and challenges of life in exile.
Keywords: Exile; activism; Bahrain; repression; political voice; Hirschman; qualitative interviewing